2004
DOI: 10.1103/physrevb.69.161303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental realization of the one qubit Deutsch-Jozsa algorithm in a quantum dot

Abstract: We perform quantum interference experiments on a single self-assembled semiconductor quantum dot. The presence or absence of a single exciton in the dot provides a qubit that we control with femtosecond time resolution. We combine a set of quantum operations to realize the singlequbit Deutsch-Jozsa algorithm. The results show the feasibility of single qubit quantum logic in a semiconductor quantum dot using ultrafast optical control.PACS numbers: 78.55. Cr,03.67.Lx Time-resolved optical spectroscopy in semi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
1
50
1
1
Order By: Relevance
“…39,40,42 However, a recent study revealed that the memory effects of a non-Markovian environment can be regarded as important physical resources 28,33 to improve QIP in an open quantum system. To further enhance the POS of the RDJA, we utilized the memory effects of the non-Markovian environment, which can be extracted by the DD method 26,39 to mitigate imperfect operations and decoherence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…39,40,42 However, a recent study revealed that the memory effects of a non-Markovian environment can be regarded as important physical resources 28,33 to improve QIP in an open quantum system. To further enhance the POS of the RDJA, we utilized the memory effects of the non-Markovian environment, which can be extracted by the DD method 26,39 to mitigate imperfect operations and decoherence.…”
Section: Resultsmentioning
confidence: 99%
“…The RDJA can be decomposed into two different unitary transformations: rotation operation and phase-controlled gate. 39,40,42 The rotation operation can be realized by a (π/2) X pulse resonant with the transition between 0 j i and 1 j i. Here ϕ X(Y) denotes the rotation with angle ϕ around the X(Y) axis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations